Type II Restriction of Bacteriophage DNA With 5hmdU-Derived Base Modifications - Flodman, Kiersten; Tsai, Rebecca; Xu, Michael Y.; Corrêa, Ivan R.; Copelas, Alyssa; Lee, Yan-Jiun; Xu, Ming-Qun; Weigele, Peter; Xu, Shuang-yong (Frontiers in Microbiology, 2019)
To counteract bacterial defense systems, bacteriophages (phages) make extensive base modifications (substitutions) to block endonuclease restriction. Here we evaluated Type II restriction of three thymidine (T or 5-methyldeoxyuridine, 5mdU) modified phage genomes: Pseudomonas phage M6 with 5-(2-aminoethyl)deoxyuridine (5-NedU), Salmonella phage ViI (Vi1) with 5-(2-aminoethoxy)methyldeoxyuridine (5-NeOmdU) and Delftia phage phi W-14 (a.k.a. W-14) with -putrescinylthymidine (putT). Among >200 commercially available restriction endonucleases (REaes) tested, phage M6, ViI, and phi W-14 genomic DNAs (gDNA) show resistance against 48.4%, 71.0%, and 68.8% of Type II restrictions, respectively. Inspection of the resistant sites indicates the presence of conserved dinucleotide TG or TC (TS, S=C or G), implicating the specificity of TS sequence as the target that is converted to modified base in the genomes. We also tested a number of DNA methyltransferases (MTases) on these phage DNAs and found some MTases can fully or partially modify the DNA to confer more resistance to cleavage by REases. Phage M6 restriction fragments can be efficiently ligated by T4 DNA ligase. Phi W-14 restriction fragments show apparent reduced rate in E. coli exonuclease III degradation. This work extends previous studies that hypermodified T derived from 5hmdU provides additional resistance to host-encoded restrictions, in parallel to modified cytosines, guanine, and adenine in phage genomes. The results reported here provide a general guidance to use REases to map and clone phage DNA with hypermodified thymidine.